If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -3(7) + 2 Multiply -3 * 7 y = -21 + 2 Combine like terms: -21 + 2 = -19 y = -19 Solving y = -19 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -19
| 17x+2-13=18x+28+12x | | 30-2s=45 | | 3(2y-6)=78 | | x-3+0.7=-2.7 | | x-3+0.7=2.7 | | 51.50=3.5x-15 | | 5(3x-4)=70 | | 3y/y-y/2=5 | | 3(7h+9)=-15 | | 2+3x=2x+4 | | 2+x=6x-16 | | 10.7x+91.71=-9.3x+90.97 | | -31=-6x-9 | | 28+32c=92 | | 0.3+0.6m=0.6m-0.6 | | -3x+7=-28 | | 21.31=1.00x+4.31 | | X+3=-21+5x | | 15-2w=w+12w | | 2x-20=3x+10 | | x+25=34.50 | | 10x+50=8x+60 | | 3x+25=50 | | 0.666666666666667x-0.166666666666667=0.5+0.833333333333333 | | y=2.65(200)+4.50 | | 19=7r-2(3+4r) | | x^2+75=2x^2 | | 2x+1=6x-35 | | 4n-11=-3 | | 8n=-3m+l | | 200=2.65x+4.50 | | v+1=v+6 |